Cost-effectiveness of dual-mobility components in patients with displaced femoral neck fractures. (1st December 2021) - Montgomery, Spencer; Bourget-Murray, Jonathan; You, Daniel Z.; Nherera, Leo; Khoshbin, Amir; Atrey, Amit; Powell, James Nelson
Abstract : Aims: Total hip arthroplasty (THA) with dual-mobility components (DM-THA) has been shown to decrease the risk of dislocation in the setting of a displaced neck of femur fracture compared to conventional single-bearing THA (SB-THA). This study assesses if the clinical benefit of a reduced dislocation rate can justify the incremental cost increase of DM-THA compared to SB-THA. Methods: Costs and benefits were established for patients aged 75 to 79 years over a five-year time period in the base case from the Canadian Health Payer's perspective. One-way and probabilistic sensitivity analysis assessed the robustness of the base case model conclusions. Results: DM-THA was found to be cost-effective, with an estimated incremental cost-effectiveness ratio (ICER) of CAD 46, 556 (£27, 074) per quality-adjusted life year (QALY). Sensitivity analysis revealed DM-THA was not cost-effective across all age groups in the first two years. DM-THA becomes cost-effective for those aged under 80 years at time periods from five to 15 years, but was not cost-effective for those aged 80 years and over at any timepoint. To be cost-effective at ten years in the base case, DM-THA must reduce the risk of dislocation compared to SB-THA by at least 62%. Probabilistic sensitivity analysis showed DM-THA was 58% likely to be cost-effective in the base case. Conclusion: Treating patients with a displaced femoral neck fracture using DM-THA components may be cost-effective compared to SB-THA in patients aged under 80 years. However, future research will help determine if the modelled rates of adverse events hold true. Surgeons should continue to use clinical judgement and consider individual patients' physiological age and risk factors for dislocation. Cite this article: Bone Joint J 2021;103-B(12):1783–1790.